Simple but efficient synthesis of novel substituted benzimidazoles over ZrO2-Al2O3. Issue 18 (16th September 2016) - Thimmaraju, N.; Shamshuddin, S. Z. Mohamed; Pratap, S. R.; Raja, K.; Shyamsundar, M.; Mohankumar, T. E.
ABSTRACT: Solid-acid catalytic materials such as ZrO2 -Al2 O3 containing 80 mol% of ZrO2 were prepared by the solution combustion method (SCM) using different fuels such as urea, hexamethylene tetramine, glycine, and sucrose. All the prepared solid acid catalytic materials were characterized for their physico-chemical properties like crystalinity, acidity, functionality and morphology. These materials were evaluated for their catalytic activity in the synthesis of a series of novel substituted benzimidazoles. The reaction conditions were optimized by varying the solvents, reaction temperature, weight of solid acid catalyst, molar ratio of the reactants, and reaction time. The ZrO2 -Al2 O3 solid acid catalytic material prepared by urea as a fuel was found to be highly active, recyclable, and reusable in the synthesis of benzimidazoles. A possible reaction mechanism for the synthesis of benzimidazoles is also proposed. GRAPHICAL ABSTRACT: